Pengaruh Kepemimpinan dan Pemberian Tunjangan Kinerja Terhadap Kinerja Pegawai Negeri Sipil Pada Kantor Kementerian Agama - Nurnaningsih, Nurnaningsih; Putra, Pand (Amsir Management Journal, 2022)
Leadership and Provision of Performance Allowances for the Performance of Civil Servants at the Office of the Ministry of Religion, Maros Regency. This study aims to determine and analyze how much influence Leadership and Performance Allowances have on the Performance of Civil Servants at the Office of the Ministry of Religion in Maros Regency. The analytical method used in this research is the method of observation, interviews, questionnaires and documentation, and the method of determining the sample used is the census sampling method of 45 samples. The analytical method used is the method of multiple linear regression (multi-linear regression). The study results show that the partial effect on the performance of employees of the Office of the Ministry of Religion in Maros Regency is the Leadership variable with a tcount of 3.978 > ttable of 2.01808, the Performance Allowance variable has no significant effect. Leadership and Performance Allowances simultaneously have a significant effect with a Fcount value of 23.588 > Ftable 3.22 on the Performance of Office Employees of the Ministry of Religion, Maros Regency.